Microbially Induced Mineralization of Layered Mn Oxides Electroactive in Li Batteries - Galezowski, Laura; Recham, Nadir; Larcher, Dominique; Miot, Jennyfer; Skouri-Panet, Fériel; Guyot, François (Frontiers in Microbiology, 2020)
Nanoparticles produced by bacteria, fungi or plants generally have physicochemical properties such as size, shape, crystalline structure, magnetic properties and stability difficult to obtain by chemical synthesis. For instance, Mn(II)-oxidizing organisms promote the biomineralization of manganese oxides with specific textures, under ambient conditions. Controlling their crystallinity and texture may offer environmentally relevant routes of Mn-oxide synthesis with potential technological applications, e.g. for energy storage. However, whereas the electrochemical activity of synthetic (abiotic) Mn-oxides has been extensively studied, electroactivity of Mn-biominerals has been seldom investigated yet. Here, we evaluated the electroactivity of the biologically induced biominerals produced by the Mn(II)-oxidizer bacteria Pseudomonas putida strain MnB1. For this purpose, we explored the mechanisms of Mn biomineralization, including kinetics of Mn(II) oxidation, under different conditions. Manganese speciation, biomineral structure and texture as well as organic matter content were determined by a combination of X-ray diffraction, electron and X-ray microscopies and thermogravimetric analyses coupled to mass spectrometry. Our results evidence the formation of an organic-inorganic composite material and a competition between enzymatic (biotic) oxidation of Mn(II) to Mn(IV) yielding MnO2 birnessite and abiotic formation of Mn(III), which ratio depends on oxygenation levels and activity of the bacteria. We reveal that a subtle control over the conditions of the microbial environment orients the birnessite to Mn(III)-phases ratio and the porosity of the assembly, which both strongly impact the bulk electroactivity of the composite biomineral. Electrochemical properties were tested in lithium battery configuration and exhibit very appealing performances (voltage, capacity, reversibility, power capability) thanks to the specific texture resulting from the microbially-driven synthesis route. Given that such electroactive Mn-biominerals are widespread in the environment, our study opens an alternative route for the synthesis of performant electrode materials under environment-friendly conditions.